Big data in wildlife research: remote web-based monitoring of hibernating black bears - Laske, Timothy G (BMC Physiol, 2014)
BACKGROUND: Numerous innovations for the management and collection of “big data” have arisen in the field of medicine, including implantable computers and sensors, wireless data transmission, and web-based repositories for collecting and organizing information. Recently, human clinical devices have been deployed in captive and free-ranging wildlife to aid in the characterization of both normal physiology and the interaction of animals with their environment, including reactions to humans. Although these devices have had a significant impact on the types and quantities of information that can be collected, their utility has been limited by internal memory capacities, the efforts required to extract and analyze information, and by the necessity to handle the animals in order to retrieve stored data. RESULTS: We surgically implanted miniaturized cardiac monitors (1.2 cc, Reveal LINQ™, Medtronic Inc.), a newly developed human clinical system, into hibernating wild American black bears (N = 6). These devices include wireless capabilities, which enabled frequent transmissions of detailed physiological data from bears in their remote den sites to a web-based data storage and management system. Solar and battery powered telemetry stations transmitted detailed physiological data over the cellular network during the winter months. The system provided the transfer of large quantities of data in near-real time. Observations included changes in heart rhythms associated with birthing and caring for cubs, and in all bears, long periods without heart beats (up to 16 seconds) occurred during each respiratory cycle. CONCLUSIONS: For the first time, detailed physiological data were successfully transferred from an animal in the wild to a web-based data collection and management system, overcoming previous limitations on the quantities of data that could be transferred. The system provides an opportunity to detect unusual events as they are occurring, enabling investigation of the animal and site shortly afterwards. Although the current study was limited to bears in winter dens, we anticipate that future systems will transmit data from implantable monitors to wearable transmitters, allowing for big data transfer on non-stationary animals.